Odpowiedź :
y = (x + 1)² - 4
y = -x - 3
y=x²+2x+1-4
y = -x - 3
-x - 3=x²+2x-3
0=x²+3x
0=x(x+3)
x=0 x=-3
y=-3 y=0
y = -x - 3
y=x²+2x+1-4
y = -x - 3
-x - 3=x²+2x-3
0=x²+3x
0=x(x+3)
x=0 x=-3
y=-3 y=0
{y = (x + 1)² - 4
{y = -x - 3
{y = x²+2x+1-4
{y = -x-3
{-x-3 = x²+2x+1-4
{y = -x-3
{-x²-3x=0
{y = -x-3
{-x(x+3)=0
{y = -x-3
{x=0 ∨ x=-3
{y = -3 ∨ y = 0
{y = -x - 3
{y = x²+2x+1-4
{y = -x-3
{-x-3 = x²+2x+1-4
{y = -x-3
{-x²-3x=0
{y = -x-3
{-x(x+3)=0
{y = -x-3
{x=0 ∨ x=-3
{y = -3 ∨ y = 0
y = (x + 1)² - 4
y = -x - 3
-x-3=x²+2x+1-4
y=-x-3
-x-x²-2x=1-4+3
-3x-x²=0
x=-3 y=0 lub y=-3 x-0
y = -x - 3
-x-3=x²+2x+1-4
y=-x-3
-x-x²-2x=1-4+3
-3x-x²=0
x=-3 y=0 lub y=-3 x-0